Prodrug Approach: NSAID Conjugates of Platinum Compounds as Anti-Cancer Agents - B, NIJA (Iraqi Journal of Pharmaceutical Sciences, 2023)
Prodrug based synthetic approach is a very promising area of research to enhance the pharmaco–kinetic and pharmaco-dynamic properties of the drugs with the remarkable reduction of the side effects. Prodrug can be used for drugs which are having poor solubility, poor transport properties, production of chronic side effects thus this approach provides a powerful tool for novel drug conjugate with improved therapeutic value. Platinum based anti-neoplastic agents are widely used in chemotherapeutic regimen but the side effects like hepatotoxicity, ototoxicity, cardiotoxicity, nausea and vomiting, diarrhea, mucositis, stomatitis, pain, alopecia, anorexia, cachexia, cytopenias and asthenia were reported. So the development of prodrugs by using platinum compounds and Non-steroidal anti-inflammatory drugs showed better therapeutic value with the reduction of side effects. Non-steroidal anti-inflammatory drugs are broad class of drugs showed Analgesic, Anti–inflammatory and Anti-pyretic activities based on the mechanism of cyclooxygenase (cox-1 and cox-2) enzyme inhibition and formation of prostaglandins. Also Non-steroidal anti-inflammatory drugs have different targets to elicit various pharmacological actions and are beneficial for many other diseases. The different targets are nuclear factor kappa B(NF-Κb), Peroxisome proliferator-activated receptors(PPAR), Mammalian target of rapamycin(mTOR), Autophagy, Cytochrome c, NSAID activated gene (NAG-1), Angiogenesis, Resolvins, Protectins, Maresins. This review focused on the development of platinum prodrugs by conjugating with different NSAIDs and the therapeutic applications of the developed novel molecules including dual action and triple action prodrugs. This review discussed the different aspects of prodrug based approach, Detail mechanism and other molecular targets of NSAIDs and the development of the platinum compounds –NSAID prodrugs.